Pengaruh Label Halal terhadap Minat Masyarakat pada Produk Makanan dan Minuman di Kabupaten Bangkalan - Aisatur Rodiyah; Faizal Amir; Fajar (Prodi Ekonomi Syariah Universitas Majalengka, 2023)
A halal label is the giving of a halal sign or written proof as a guarantee on product packaging to show that the food and beverage product is permissible for consumption and has a halal status. The halal label indirectly shows and explains that products that are labeled halal are products that are safe, reliable and do not contain anything illegal. The purpose of this research is to find out how the image of a halal label affects people's interest in Bangkalan Regency and to find out the effect of a halal label on people's interest in food and beverage products in Bangkalan Regency. For the place where the researcher did it,namely in Bangkalan Regency, this study used a quantitative approach descriptive analysis method. Sampling using non probability sampling technique, namely accidental sampling technique. Test the instrument data, namely test validity and reliability, while the data analysis using simple linear regression analysis with the help of IBM SPSS Statistics version 20. Respondents were selected as many as 80 respondents. The results of this study indicate that the halal label (X) has a significant and significant effect on public interest (Y) in Bangkalan Regency. Where thitung > ttabel that is thitung 7,570 > ttabel 2,640 dan nilai sig 0,000 < dari 0,05. So it can be concluded that the hypothesis Ho is rejected and Ha is accepted. This has proven that the inclusion of a halal label on products provides a positive value in influencing public interest in Bangkalan Regency.